2009
DOI: 10.1097/eja.0b013e3283269ff4
|View full text |Cite
|
Sign up to set email alerts
|

Learning curves of the Glidescope, the McGrath and the Airtraq laryngoscopes: a manikin study

Abstract: In a 'normal airway' model, intubation skills with the new devices appeared to be rapidly mastered. The three indirect laryngoscopes provided a better glottic exposure than the Macintosh. The Airtraq displayed the most favourable learning curve, probably reflecting differences in the techniques of endotracheal tube placement: guiding channel versus steering technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 17 publications
4
63
0
1
Order By: Relevance
“…As in our study, another study reported that medical students preferred the Glidescope as their first choice (11)(12)(13)(14). All two video-laryngoscopes had a short learning curve and provided higher first intubation success rates in non-experienced hands, even in normal and difficult airways (15,16). However, all of them were performed in an adult population or adult manikin.…”
Section: Discussionsupporting
confidence: 60%
“…As in our study, another study reported that medical students preferred the Glidescope as their first choice (11)(12)(13)(14). All two video-laryngoscopes had a short learning curve and provided higher first intubation success rates in non-experienced hands, even in normal and difficult airways (15,16). However, all of them were performed in an adult population or adult manikin.…”
Section: Discussionsupporting
confidence: 60%
“…In case of failure in providing airway within 2 min or failure in completing the procedure, the oesophageal intubation was considered unsuccessful. As in the study of Savoldelli et al (14), this study used the method of grading the applied pressure on teeth for measuring the severity of dental trauma: grade 0, no pressure; grade 1, mild; grade 2, moderate and grade 3, severe pressure. The participants were asked to reply to the question: 'If you consider the ease of use and learnability, which instrument would you prefer to use for intubation?'…”
Section: Methodsmentioning
confidence: 99%
“…Lees et al demonstrated a learning curve over 20 intubations in children in expert anaesthetists, but reported an incidence of failed intubations higher than with direct laryngoscopy, again raising substantial doubts that expertise had been reached [14]. Savoldelli et al also defined a list of criteria, including Cormach and Lehane grade, subjective difficulty and number of attempts to represent the complexity of intubation task, with both direct and videolaryngoscopy [15].…”
Section: Introductionmentioning
confidence: 99%